Freedom has a face : race, identity, and community in Jefferson's Virginia - Von Daacke, Kirt, 1968- (Carter G. Woodson Institute series., 2012)
This book tells the stories of free blacks who worked hard to carve out comfortable spaces for existence. They were denied full freedom, but they were neither slaves without masters nor anomalies in a society that had room only for black slaves and free white citizens. A typical rural Piedmont county, Albemarle was not a racial utopia. Rather, it was a tight-knit community in which face-to-face interactions determined social status and reputation. A steep social hierarchy allowed substantial inequalities to persist, but it was nonetheless an intimately interracial society.